Assessment of Coal Permeability using Injection Falloff Test and Effect of Temperature and Skin Factor on It: A Case Study for Coal Seams of Jamalganj Coalfield, Bangladesh - Hasan, Md Fuad; Rahman, Md Mahabubur; Ullah Bulbul, Md Atik; Biswas, Arup Kumar; Farhad, MIM; Rahman, Md Aminur (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The Jamalganj coalfield with the coal deposits of the Permian Gondwana Group in the halfgraben basin was discovered in Joypurhat District, Northwestern Bangladesh, sometime in 1962. Individual coalbed thickness ranges from 0.60 m to 42 m and seams were encountered between the depth ranges of 640 m and 1158 m. Since mining has not yet begun due to the greater depth of the coal seams, several researchers have proposed a Coalbed Methane (CBM) exploration in this region. This research focuses on the permeability of the Jamalganj coal derived from the in-situ Injection Falloff Test (IFT), which is an important reservoir parameter and one of the key factors in CBM exploration and Underground Coal Gasification (UCG). In addition to that, the relationship of temperature and skin factor with permeability is one of the key findings of this research, permeability obtained from the IFT ranges from 2.57 to 121.16 mD while the skin factor ranges from - 6.11 to 50.85 and a higher temperature gradient as of about 4°C per 100 m depths was observed. The study shows that temperature has an inverse relationship with the permeability that decreases with depth and temperature increases, which is analogous with the other CBM producing reservoirs around the world. The negative skin factor denotes flow enhancement near the wellbore and a well-stimulated reservoir, and the positive skin factor indicates increased flow resistance near the wellbore, which reduces permeability. The permeability data suggest that the analyzed coal seams of the Jamalganj Coalfield are suitable for unconventional gas production by either CBM or UCG development. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 103-112